Intrauterine Fetal Death and the COVID-19 Pandemic: Looking beyond SARS- CoV-2 Infection - Yasmin, Farida; Hosain, Nazmul; Haque, Nadira; Hasan, Tamanna; Aurora, Aphrodity (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2024)
Background: COVID-19 pandemic has caused high numbers of deaths and complications since 2020. Though the risk is the same as in the general population, pregnant women with COVID-19 are especially susceptible to developing complications because of their altered physiology. The objective of this retrospective study is to investigate the relationship betweenthe COVID-19 pandemic period and intrauterine fetal death, which can help to take steps to reduce intrauterine fetal death during the pandemic. Materials and methods: This retrospective study compared the intrauterine fetal death rate during the pre-pandemic (March 01, 2019 to February 29, 2020) and the pandemic period (March 01, 2020, to February 28, 2021) in a tertiary referral hospital in Bangladesh. Patient data were collected from the record-keeping register of the Department of Obstetrics and Gynecology and analyzed by computer-based software presented in graph, chart and table. Results: Out of 21717 obstetric patients admitted patients,821 (3.78%) were documented as cases of intrauterine fetal death in the pre-pandemic period, whereas in the pandemic period, the number was 895 (4.86%) out of 18424. Due to inadequate data records and considering the exclusion criteria, a total of 790 IUFD patients of the pre-pandemic period and 860 IUFD patients of the pandemic period were included in this study. Conclusion: The percentage of IUFD on obstetric admission showed significantly (p<0.001) higher in the pandemic period compared to that in the pre-pandemic period. This result is important for providing insights to the policy makers for future planning, counseling of women wishing to become pregnant, and prioritizing their safety, including their vaccination. Chatt Maa Shi Hosp Med Coll J; Vol.22 (2); July 2023; Page 47-50